DRUG FOR PROMOTING REPRODUCTION OF PERIODONTIUM - MATSUURA MASAYASU; WATANABE SHIGEYUKI; IKADA YOSHITO; GEN JIYOUKIYUU; KITA KAZUYOSHI (1992)
PURPOSE:To obtain the subject drug, consisting essentially of a urethane prepolymer formed from an aliphatic polyester such as polylactic acid and a diisocyanate and capable of reproducing pericemental membranes destroyed by periodontitis and promoting adhesion of normal roots of teeth to connective tissues. CONSTITUTION:A drug for promoting reproduction of periodontia consisting essentially of a urethane prepolymer formed from an aliphatic polyester, selected from the group consisting of polylactic acid, polyglycolic acid, poly-epsilon-lactone, lactic acid-glycolic acid copolymers at <=50% ratio of the lactic acid and lactic acid-epsilon-caprolactone copolymers at <=50% ratio of the lactic acid and a diisocyanate compound and having <=5000, preferably 1000-4000 molecular weight. A polyelectrolytic complex, a cell activator, an antimicrobial agent or an anti- inflammatory agent, etc., is suitably blended in the aforementioned drug and used by directly administration thereof to periodontal pockets after periodontal surgical treatment or root planing treatment.